Similarity transformation approach for a heated ferrofluid flow in the presence of magnetic field - Bognár Gabriella; Hriczó Krisztián (2018)
The aim of this paper is to investigate theoretically the magnetothermomechanical interaction between a heated viscous incompressible ferrofluid and a cold wall in the presence of a spatially varying field. Similarity transformation is used to convert the governing non-linear boundary-layer equations into coupled nonlinear ordinary differential equations. These equations are numerically solved using a discretization scheme using higher derivative method (HDM). The effects of governing parameters corresponding to various physical conditions are analyzed. Numerical results are obtained for distributions of velocity and temperature, the dimensionless wall skin friction and heat-transfer coefficients. The results indicate that two solution exists in some cases. A comparison with previous studies available in the literature has been done and we found an excellent agreement with it.